2021
DOI: 10.1021/acsphotonics.0c01728
|View full text |Cite
|
Sign up to set email alerts
|

Markedly Improved Performance of Optically Pumped Organic Lasers with Two-Dimensional Distributed-Feedback Gratings

Abstract: Continuous-wave (CW) lasing is still difficult to realize in organic laser dyes, one reason being the thermal degradation caused by intense photoexcitation. A decrease in laser threshold suppresses the thermal degradation and, therefore, leads to long-lasting lasing from organic laser dyes. Here, we show that it is possible to decrease the laser thresholds by combining the organic laser dye 4,4-bis­[(N-carbazole)­styryl]­biphenyl, which has a small spectral overlap between the laser emission and the excited-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 57 publications
(121 reference statements)
0
22
0
Order By: Relevance
“…Systematic progress toward a low loss OSLD resonator began with the Fabry–Perot architecture proposed by Kozlov et al, but it has since focused mainly on DFB gratings since they facilitate straightforward integration of electrical contacts and have enabled the lowest threshold optically pumped OSLs to date. , ,, In exploring the impact of electrical contacts on the threshold of second-order polymer DFB lasers, Reufer et al found that the combination of a thick Ag bottom grating and a thin (20 nm) ITO top contact led to only a minor (∼20%) increase in the threshold excitation density relative to a contact-free control (Figure ). Interestingly, the Ag bottom grating on its own (with no ITO top contact) had a ∼30% lower threshold density relative to the control, presumably because the associated increase in DFB coupling coefficient outweighs the added dissipation loss from the metal, as suggested by a more pronounced Bragg dip in the PL spectrum.…”
Section: Organic Semiconductorsmentioning
confidence: 99%
“…Systematic progress toward a low loss OSLD resonator began with the Fabry–Perot architecture proposed by Kozlov et al, but it has since focused mainly on DFB gratings since they facilitate straightforward integration of electrical contacts and have enabled the lowest threshold optically pumped OSLs to date. , ,, In exploring the impact of electrical contacts on the threshold of second-order polymer DFB lasers, Reufer et al found that the combination of a thick Ag bottom grating and a thin (20 nm) ITO top contact led to only a minor (∼20%) increase in the threshold excitation density relative to a contact-free control (Figure ). Interestingly, the Ag bottom grating on its own (with no ITO top contact) had a ∼30% lower threshold density relative to the control, presumably because the associated increase in DFB coupling coefficient outweighs the added dissipation loss from the metal, as suggested by a more pronounced Bragg dip in the PL spectrum.…”
Section: Organic Semiconductorsmentioning
confidence: 99%
“…The state─ of─ the─ art DFB resonators include mixed─ order DFB structures in which the feedback occurs in the 1 st order DFB, and the light emission occurs from the 2 nd order DFB, leading to the surface emission with a low threshold. 6 Further, the DBRs that are sequential multilayers of high and low refractive index materials provide high re ectivity and low absorption compared to the conventional metallic mirrors, providing a verti-cal─ cavity surface─ emitting laser (VCSEL) (Figure 2e), where the optical feedback is in the direction perpendicular to the laser surface. 2,3,5 In addition, the micro─ ring (Figure 2f) and micro─ sphere (Figure 2g) lasers are ring─ shaped and spherical waveguides including a gain medium that traps light and recirculates it to provide optical feedback based on the constructive interference of light in the resonators, respectively.…”
Section: Materials Design Of Organic Lasers Aimed At Low Lasing Thres...mentioning
confidence: 99%
“…Introducing interface cracks is an intriguing strategy to manipulate optical scattering and diffraction for the improvement of lasing performances [ 27 ]. Although interface cracks usually decrease mechanical toughness and carrier mobility [ 28 ], they can intrinsically possess large refractive index contrast (∆ n > 0.5 to 0.8) to act as natural cavities [ 29 ].…”
Section: Introductionmentioning
confidence: 99%